Necesidad de reformar el artículo 135 del Código del Trabajo para garantizar el derecho a la educación de los adolescentes trabajadores - Caguana Ordóñez, Wilson Amador (2015)
Given the socioeconomic circumstances affecting much of Ecuadorian households, despite the desire to eradicate the labor participation of children and adolescents, the Constitution of the Republic of Ecuador recognizes the locked adolescent and older adolescents fifteen years should be fulfilled in an exceptional way and so does not conflict with their right to education. Being necessary to emphasize that under the same Constitution, the State's duty to ensure universal and compulsory access of all people to education, in the initial, basic, and high school or equivalent is established. Knowing that the participation of adolescents over fifteen years in business activities based on a relationship of dependency, the Lab our Code regulates that adolescents and young workers who have not completed basic education, must have two hours of working hours so they can attend school, this law shall be recognized by their employers. Obviously, there is a legal contradiction, since the Lab our Code, determines that the employer is required to allow the attendance of those young workers over fifteen years who have not completed their basic education, whereas available the Constitution of the Republic of Ecuador, the State is obliged to ensure that all people have access to education to the baccalaureate level or equivalent. This contradiction creates legal uncertainty regarding the transcendental right to access to education, creating the possibility that the same is violated, so a legal problem, which is the subject matter of this work is generated called "NEED FOR REFORM ARTICLE 135 OF THE CODE OF WORK TO ENSURE THE RIGHT TO EDUCATION OF TEEN WORKERS ". The research consists of a conceptual, doctrinal, legal and comparative law, which is part of the literature review theoretical analysis; by the description of the methodological resources; the presentation of the results of the field work; verification objectives and hypothesis testing; findings, recommendations and proposed legal reform of the Lab our Code, through which it aims to ensure a more efficient way the rights of adolescent girls and young workers, education